In situ one-pot formation of crown ether functionalized polysulfone membranes for highly efficient lithium isotope adsorptive separation. (December 2018) - Pei, Hongchang; Yan, Feng; Ma, Xiaohua; Li, Xianhui; Liu, Congcong; Li, Jianxin; Cui, Zhenyu; He, Benqiao
Graphical abstract: Highlights: One-pot grafting and formation method was proposed to prepare PSf- g -AB15C5 membrane. Grafting and self-crosslinking led to an increase in the viscosity of the solution. The membrane can be formed even at a very low polymer solution concentration of 10%. The sponge-like crosslinked networks displayed a strong mechanical strength. A remarkable equilibrium separation factor of 6 Li + / 7 Li + up to 1.055 was obtained. Abstract: A unique one-pot polymer synthesis and membrane formation technique was developed to fabricate polysulfone-graft-4′-aminobenzo-15-crown-5-ether (PSf-g-AB15C5) membranes for lithium isotope adsorptive separation. This is, the reaction system and the preparation of casting solution were integrated into one step without separation and purification of the product. Herein, PSf-g-AB15C5 was prepared by the grafting reaction of AB15C5 and chloromethylated polysulfone (CMPSf). The viscosity of reaction solution was controlled by the grafting time. The reaction solution with a certain viscosity or at a certain grafting time as a casting solution was in-situ cast to porous membranes through non-solvent induced phase separation (NIPS). Results showed that the resultant membrane structures changed gradually from macrovoids to sponge-like with the viscosity increase of the reaction solution, which is attributed to the grafting and self-crosslinking of PSf-g-AB15C5 polymers. This endows the membranes can be formed even at a very low polymer solution concentration of 10%. Interestingly, the sponge-like crosslinked networks displayed a strong mechanical strength at the range of 2.12–3.72 MPa. Moreover, all membranes showed high porosity. Especially, the membrane with the reaction time of 20 h exhibited a remarkable porosity of 85.2%. These porous membranes promoted the effective adsorption between Li + ions and crown ether groups and led to a high distribution coefficient. A remarkable equilibrium separation factor of 6 Li + / 7 Li + up to 1.055 was obtained from the membrane containing 0.521 mmol g −1 of the immobilization crown ether, which is much higher than the acceptable industrial scale separation factor of 1.03. Due to the higher affinity of 6 Li + to crown ether than 7 Li +, 6 Li + and 7 Li + were enriched in the membrane phase and the solution phase, respectively. Therefore, the membrane shows a great potential in the development of green and highly efficient membrane chromatography for lithium isotope adsorptive separation applications.